Hacia una justicia administrativa efectiva para la protección del justiciable - Carmona Calderón, Ma. Constancia (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
Among the obligations that the Mexican state has in the American Convention on Human Rights is that of adopting the legislative measures that are necessary to make effective the human rights provided therein, as indicated in Article 2 of the Pact of San José. Constitutional procedural law concentrates the guidelines, guidelines, principles and basic rights that secondary legislation must observe so that the process constitutes an effective and fair means for the resolution of legal disputes. The contentious administrative process in Mexico is the means of defense that is followed before the Federal Court of Administrative Justice, its objective is to resolve controversies that arise between the Public Administration and individuals. The procedural constitutional law for administrative litigation in Mexico is defined as the set of relationships, guidelines, directives, principles and basic rights established in the constitution and the international treaties to which Mexico is a party, which outline the parameters that the legislation must contemplate. secondary so that this process constitutes an effective resource for the resolution of legal controversies between the Federal Public Administration and the governed. It is made up of three groups of rights: Those concerning the process in general provided for in the Political Constitution of the United Mexican States; the special guidelines contained in articles 73, section XXIX-H and 104 section III, of the same regulatory body and; the human rights - related to the process - contemplated in the international treaties signed by Mexico, specifically the judicial guarantees and the right to judicial protection contemplated in articles 8 and 25 of the American Convention on Human Rights.

Entre las obligaciones que tiene el estado mexicano en la Convención Americana sobre Derechos Humanos se encuentra la de adoptar las medidas legislativas que fueren necesarias para hacer efectivos los derechos humanos ahí previstos, tal y como lo indica el artículo 2° del Pacto de San José. El derecho procesal constitucional concentra los lineamientos, directrices, principios y derechos básicos que debe observar la legislación secundaria a fin de que el proceso constituya un medio eficaz y justo para la resolución de controversias jurídicas. El proceso contencioso administrativo en México es el medio de defensa que se sigue ante el Tribunal Federal de Justicia Administrativa, tiene por objetivo dirimir las controversias que se susciten entre la Administración Pública y los particulares. El derecho constitucional procesal para el contencioso administrativo en México se define como el conjunto de relaciones, lineamientos, directrices, principios y derechos básicos establecidos en la constitución y los tratados internacionales de los que México sea parte, que trazan los parámetros que debe contemplar la legislación segundaria a fin de que este proceso constituya un recurso efectivo para la resolución de las controversias jurídicas entre la Administración Pública Federal y los gobernados. Se integra por tres grupos de derechos: Los concernientes al proceso en general previstos en la Constitución Política de los Estados Unidos Mexicanos; las directrices especiales a que contraen los artículos 73, fracción XXIX-H y 104 fracción III, del mismo cuerpo normativo y; los derechos humanos -relativos al proceso- contemplados en los tratados internacionales suscritos por México, concretamente las garantías judiciales y el derecho de protección judicial contemplados en los artículos 8° y 25 de la Convención Americana sobre Derechos Humanos.
Facultad de Derecho y Ciencias Sociales. Doctorado en Ciencias Jurídicas
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19005; info:eu-repo/classification/cti/5; FDCS-D-2024-1478; Proceso contencioso administrativo; Derecho constitucional procesal; Recurso judicial efectivo